Epidemiological and clinical presentation of head and neck neoplasia: a review - Munjal, Manish; Munjal, Shubham; Saggar, Vanshika; Kaur, Hardeep; Arora, Vineeta; Sandhu, Lovleen; Binepal, Tegbir Singh; Bharadwaj, Iti; Arora, Anurima; Mehta, Devambika; Pillai, Anjana (International Journal Of Community Medicine And Public Health, 2023)
Head and neck squamous cell carcinoma (HNSCC) stand at the sixth position most, amongst all the malignancies worldwide. Neoplasms arising in the oral cavity, larynx, pharynx, salivary gland and nasal cavity are all included in the head and neck malignancies. More than 90% of malignancies of the oral cavity are squamous cell carcinomas (SCC). Among the four head neck cancer sub-sites combined, the mean age at the time of diagnosis has risen, in the last four decades. Studies have documented a male predilection. A small percentage of SCC cases are inherited or are familial. Cigarette smoking, alcohol consumption, betel quid chewing, poor nutrition, poor oral hygiene, HPV, Epstein-Barr virus and Candida albicans infections are the etiological agents who have the ability to cause HNSCC. Non healing ulcer, difficulty in swallowing, change in voice, swelling, sore throat- that doesn’t get better- are the symptoms of head and neck cancers. Moreover, there may be unusual bleeding, facial swelling or difficulty in breathing.